2019
DOI: 10.21273/horttech04320-19
|View full text |Cite
|
Sign up to set email alerts
|

Adult and Child Focus Group Views of Oranges and Mandarins

Abstract: To identify factors that may reduce mandarin (Citrus reticulata) and orange (Citrus sinensis) consumer acceptance and to acquire information on current consumer thoughts and perceptions, a series of eight focus groups were held in a college town in northern California: four with children and four with adults. Adults mentioned cost proportionately more (P ≤ 0.05) often than children, as well as farm to fork, purchasing pref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…Some participants expressed that the cake itself was more representative of being a dessert than the fruit. This is similar to our previous findings that fruits, such as oranges, may be viewed more as a snack than a dessert in the United States (Kurzer et al., 2019). One participant in Experiment 2 described why they selected the conventional dessert as follows: “I rarely eat dessert when cooking for myself, while I regularly eat fruit, so I generally don't classify fruit as a dessert.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Some participants expressed that the cake itself was more representative of being a dessert than the fruit. This is similar to our previous findings that fruits, such as oranges, may be viewed more as a snack than a dessert in the United States (Kurzer et al., 2019). One participant in Experiment 2 described why they selected the conventional dessert as follows: “I rarely eat dessert when cooking for myself, while I regularly eat fruit, so I generally don't classify fruit as a dessert.…”
Section: Resultssupporting
confidence: 92%
“…Fruit may also elicit emotional nostalgia (Kurzer, Bechtel, & Guinard, 2019), potentially driving the preference for the high fruit dessert. One of the participants in Experiment 1 said “My brother and I used to eat peaches, nectarines, persimmons, and grapes every day at home.…”
Section: Resultsmentioning
confidence: 99%
“…Responses related to sweetness were the most frequently mentioned, suggesting that this sensory characteristic is the most relevant for consumers' conceptualization and the most influential on their purchase decisions (14) . Previous studies conducted in USA have reported that sweetness and flavor are key drivers of consumers' willingness to purchase mandarins (7)(8) (17) . Additionally, juiciness and color were also relevant sensory characteristics for consumers' conceptualization of mandarins.…”
Section: Discussionmentioning
confidence: 99%
“…Results from the B-W scaling highlighted the importance of sensory characteristic good flavor as the most important characteristic underlying consumers' purchase decisions of mandarins. According to Kurzer and others (17) , adults feel frustrated by the lack of flavor and inconsistent sensory quality of mandarins. These results stress the need to integrate sensory and consumer science into breeding programs in order to improve marketability of new cultivars and increase consumption of mandarins (4) (18) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation